2014
DOI: 10.1177/0042098013516686
|View full text |Cite
|
Sign up to set email alerts
|

The willingness to pay for green apartments: The case of Nanjing, China

Abstract: Faced with the challenge of developing sustainable cities, the Chinese government sets green construction as part of the national strategy to reduce energy consumption. However, the consumer market has shown limited response to such policies. To upscale green building, it is crucial to understand the market demands for green apartments. This article employs a conjoint model to estimate the willingness to pay for green dwellings versus accessibility to metros and jobs and neighbourhood quality by different soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 44 publications
(55 reference statements)
2
48
0
Order By: Relevance
“…Thus, the present findings can provide useful experiences for policy makers and other institutions in other developing countries. Third, previous studies on the WTP for GH were mentioned previously in Nanjing [14] and Beijing [23], which are First-tier cities. To our knowledge, there was little research in the Second-tier cities, and therefore the findings can be extended to the mass cities in China.…”
Section: Developermentioning
confidence: 96%
See 1 more Smart Citation
“…Thus, the present findings can provide useful experiences for policy makers and other institutions in other developing countries. Third, previous studies on the WTP for GH were mentioned previously in Nanjing [14] and Beijing [23], which are First-tier cities. To our knowledge, there was little research in the Second-tier cities, and therefore the findings can be extended to the mass cities in China.…”
Section: Developermentioning
confidence: 96%
“…(3) GH affordability. Prior studies [14] reported that only rich consumers are prepared to pay for green apartments. If the construction practitioners can freely control their purchasing activities without pressure from financial expenses, then they can show strong affordability of GH.…”
Section: Hypothesis 6 (H6)mentioning
confidence: 99%
“…However, the industry has started to recognize consumers' diversifying preferences. For instance, pro-environmental behaviour (Hu et al 2013), has resulted in creating more customer-centric culture (e.g., Killip, 2013). Recently, studies on consumer's sustainability related choices towards green building have started to gain more ground (e.g.…”
Section: Introduction and Purposementioning
confidence: 99%
“…To strengthen customer acceptance of green hotels, it is crucial to investigate the potential incentives for their green demand. As hotel customers cannot obtain benefits from energy savings, their demand for green hotels depends on environmental responsibility and/or improvement in living comfort (Dastrup et al 2012, De Silva and Pownall 2014, Hu, Geertman and Hooimeijer 2014, Kahn and Kok 2014. Most studies attribute hotel customers' ecofriendly decisions to their environmental consciousness (Han, Hsu and Lee 2009, Han et al 2011, Kang et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It is necessary to take into account consumers' actual payment for green hotels (Barber 2014). Hu, Geertman and Hooimeijer (2014), studying the housing market in China, conclude that residents are only willing to pay a green premium when living comfort improves; however, little research has investigated the living comfort of green hotels. In fact, energy efficiency does not necessarily lead to reduced comfort level, and improved indoor environmental quality is a stated goal of green buildings (Cole 2000, World Green Building Council 2013.…”
Section: Introductionmentioning
confidence: 99%